2023
DOI: 10.1136/gutjnl-2022-327909
|View full text |Cite
|
Sign up to set email alerts
|

Combining ferroptosis induction with MDSC blockade renders primary tumours and metastases in liver sensitive to immune checkpoint blockade

Abstract: ObjectiveInvestigating the effect of ferroptosis in the tumour microenvironment to identify combinatory therapy for liver cancer treatment.DesignGlutathione peroxidase 4 (GPx4), which is considered the master regulator of ferroptosis, was genetically altered in murine models for hepatocellular carcinoma (HCC) and colorectal cancer (CRC) to analyse the effect of ferroptosis on tumour cells and the immune tumour microenvironment. The findings served as foundation for the identification of additional targets for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(63 citation statements)
references
References 37 publications
1
46
0
Order By: Relevance
“…The biological activity of WA in the prodrug is further restored by excessive GSH in tumour cells, thereby inducing ferroptosis in tumour cells by combining GPX 4 inhibition and releasing catalytic reactive Fe 2+ substances through the KEAP 1-NRF 2-HMOX 1 pathway. 155,156 Ferritin lysis of tumour cells also releases a large amount of DAMP and tumour derived antigens into the wound microenvironment, which are then engulfed by antigen presenting cells (APCs) such as dendritic cells (DCs) and macrophages to trigger cross presentation and activate CTL. 157 5.2.3.…”
Section: Biomaterials Sciencementioning
confidence: 99%
“…The biological activity of WA in the prodrug is further restored by excessive GSH in tumour cells, thereby inducing ferroptosis in tumour cells by combining GPX 4 inhibition and releasing catalytic reactive Fe 2+ substances through the KEAP 1-NRF 2-HMOX 1 pathway. 155,156 Ferritin lysis of tumour cells also releases a large amount of DAMP and tumour derived antigens into the wound microenvironment, which are then engulfed by antigen presenting cells (APCs) such as dendritic cells (DCs) and macrophages to trigger cross presentation and activate CTL. 157 5.2.3.…”
Section: Biomaterials Sciencementioning
confidence: 99%
“…82 Additionally, the release of HMGB1 and oncogenic KRAS protein from ferroptotic cells can promote M2 macrophage polarization in pancreatic cancer or the recruitment and activation of myeloid-derived suppressor cells (MDSCs) in mice with Gpx4-deficient liver tumors. 83,84 Furthermore, HMGB1 can potentiate the cyclic GMP-AMP synthase (CGAS)-STING1 pathway 85 and induce the expression of immune checkpoint CD274 (also known as PD-L1) through the activation of hypoxia inducible factor 1 subunit alpha (HIF1A) transcription factor in pancreatic tumor. 86 These mechanisms contribute to the establishment of an inflammation-associated immune-suppressive tumor microenvironment.…”
Section: Tumor Immunitymentioning
confidence: 99%
“…[11][12][13] Recent reports have shown that ferroptosis may enhance the antitumor efficacy of immunotherapies in cancer. [14,15] Therefore, an in-depth investigation of the mechanism of tumor ferroptosis and its regulation is crucial and may be of considerable aid in guiding clinical targeted therapy. Accumulation of lipid peroxidation products is a significant feature of ferroptosis and is regulated by the generation and elimination of lipid peroxides.…”
Section: Doi: 101002/advs202303484mentioning
confidence: 99%